2016
DOI: 10.1590/s1518-8787.2016050006208
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of fenproporex for obesity treatment: a systematic review

Abstract: OBJECTIVE To evaluate clinical evidence on the safety and efficacy of fenproporex for treating obesity.METHODS MEDLINE, LILACS and Cochrane Controlled Trials Register were searched as well as references cited by articles and relevant documents. Two authors independently assessed the studies for inclusion and regarding risk of bias, collected data, and accuracy. Eligible studies were all those placebo-controlled that provided data on the efficacy and safety of Fenproporex to treat obesity.RESULTS Only four cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…None of these drugs are marketed for the treatment of ADHD. Fenproporex, a compound with structural similarity to amphetamine and prescribed as an anorectic drug, is 60-80% converted to amphetamine in rats and humans (see review by Paumgartten, Pereira, & de Oliveira, 2016). While data on fenproporex could be considered relevant to the possible developmental effects of amphetamine, we did not locate adequate studies on human pregnancy outcomes after fenproporex exposure.…”
Section: Amphetamine Prodrugsmentioning
confidence: 99%
“…None of these drugs are marketed for the treatment of ADHD. Fenproporex, a compound with structural similarity to amphetamine and prescribed as an anorectic drug, is 60-80% converted to amphetamine in rats and humans (see review by Paumgartten, Pereira, & de Oliveira, 2016). While data on fenproporex could be considered relevant to the possible developmental effects of amphetamine, we did not locate adequate studies on human pregnancy outcomes after fenproporex exposure.…”
Section: Amphetamine Prodrugsmentioning
confidence: 99%
“…The maximal plasmatic concentration of fenproporex occurs 2–4 h post-administration and its effect lasts for 6–8 h. It has renal clearance and eliminates fully after 48 h [2,7,21,22]. Among the adverse events are glaucoma, pulmonary artery hypertension, vomiting, headaches, vertigo, tachycardia and insomnia [19].…”
Section: Fenproporexmentioning
confidence: 99%
“…A recent systematic review found only four controlled trials of fenproporex, which had in common a flawed study design with a high risk of selection, performance, and detection biases as well as incomplete outcome data 6 . Another systematic review of clinical trials of amfepramone, fenproporex, and mazindol revealed that 19 out of 25 studies included in the review showed a high risk of bias and authors' conclusion was that these drugs "…showed poor evidence of efficacy in the treatment of overweight and obese patients" 7 (p. 317).…”
mentioning
confidence: 99%
“…Besides being a risk factor for cardiovascular morbidity, amphetamines are psychostimulant drugs and may induce sleeplessness, mood changes, and psychiatric disorders. Several cases of abuse and dependence to fenproporex (converted into amphetamine in the body) were reported 6 .…”
mentioning
confidence: 99%